Analisis Pengelolaan Badan Usaha Milik Desa (BUMDes) Terhadap Kemandirian Perekonomian Masyarakat - Irmansah, Irmansah; Mulfauzi, Ratihas; Nurhasanah, Nurhasanah; Nurnazmi, Nurnazmi (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
BUMDes is a village business managed by the local government and has a legal entity with the aim of making the community economically independent and the obstacles experienced by BumDesa in carrying out its management as BumDes. This research uses descriptive qualitative research approach. Research informants are village heads, BumDes administrators and community beneficiaries of the BumDes budget. Data collection by observation, interviews and documentation. Data analysis uses data display, data verification and data validity testing, then conclusions. The results of the research are that of all the people of Ntoke Village who have used assistance from BumDes funds, on average they have become economically independent, because while using BumDesa money, the community manages it by buying cattle, buying fishing trawls, building kiosk businesses. The obstacles for BumDesa in managing its budget are that there are people who do not return the loan money according to the agreed terms, BumDesa administrators do not understand the duties and activities of BumDesa.